Out-of-Range Stray Light Characterization of Single-Monochromator Brewer Spectrophotometers. Issue 1 (1st January 2018) - Pulli, T.; Karppinen, T.; Nevas, S.; Kärhä, P.; Lakkala, K.; Karhu, J. M.; Sildoja, M.; Vaskuri, A.; Shpak, M.; Manoocheri, F.; Doppler, L.; Gross, S.; et al.
ABSTRACT: Stray light in single-monochromator Brewer instruments increases the uncertainty of solar ultraviolet spectral irradiance measurements and ozone retrievals. To study how spectral irradiance within and outside the measurement ranges of the instruments affects stray light, two Brewer MKII instruments were characterized for the level of in- and out-of-range stray light at multiple laser wavelengths. In addition, several solar-blind filters utilized in single-monochromator Brewers to limit out-of-range stray light were characterized for spectral and spatial transmittances. Finally, the measurement results were used to simulate the effect of stray light and stray light correction on spectral irradiance and ozone measurements at different wavelength regions. The effect of stray light from wavelengths above 340 nm was found to be negligible compared with other sources of uncertainty. On the other hand, contributions from wavelengths between 325 and 340 nm can form a significant portion of the overall stray light of the instrument, with 325 nm being the upper limit of the nominal measurement range of the instrument.